2009
DOI: 10.1007/s10815-008-9284-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of letrozole with continuous gonadotropins and clomiphene-gonadotropin combination for ovulation induction in 1387 PCOS women after clomiphene citrate failure: a randomized prospective clinical trial

Abstract: Purpose Letrozole, though reported to be an effective ovulation inducing agent, warrants larger randomized trials. The purpose of this study is to compare the efficacy of letrozole with that of rFSH and clomiphene citrate(CC)/rFSH for ovarian stimulation in IUI cycles. Methods Randomized, prospective, single-blinded clinical trial. 1387 PCOS women after CC failure were randomized into three groups: Group A received letrozole, Group B received CC with two doses rFSH and Group C received continuous rFSH day 2 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 29 publications
6
44
0
1
Order By: Relevance
“…In recent years, the usefulness of letrozole for ovulation induction was investigated. A number of studies found that the effect of letrozole was comparable to that of combined CC and gonadotropins and of gonadotropins alone and CC alone for the induction of ovulation (Ganesh et al, 2009;Nejad et al, 2008). Also some studies have demonstrated that some patients do not respond to letrozole as an infertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the usefulness of letrozole for ovulation induction was investigated. A number of studies found that the effect of letrozole was comparable to that of combined CC and gonadotropins and of gonadotropins alone and CC alone for the induction of ovulation (Ganesh et al, 2009;Nejad et al, 2008). Also some studies have demonstrated that some patients do not respond to letrozole as an infertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[4] However, studies have demonstrated that many anovulatory women are resistant to clomiphene citrate, failing to ovulate while utilizing the drug. [5,6,8] In patients resistant to clomiphene citrate, a common next step in treatment usually includes the use of injectable gonadotropins, with their risks of high order multiple pregnancies, ovarian hyperstimulation syndrome, painful injection sites, and demands extensive and invasive monitoring during treatment and higher cost of therapy. …”
Section: Historymentioning
confidence: 99%
“…The number of mature follicles at hCG administration was not commented upon. [5] It appears that letrozole, when used for clomiphene citrate resistant anovulatory women, confers higher pregnancy rates with lower miscarriage rates. This seems to occur even when the total number of mature follicles is lower than with clomiphene citrate.…”
Section: Chronic Anovulationmentioning
confidence: 99%
“…Эффективность летрозола сравнима с таковой при использовании рекомбинантного ФСГ для сти-муляции овуляции у женщин с СПКЯ, и, как было найдено, летрозол был подходящим и экономически рентабельным лекарственным средством для стиму-ляции [21].…”
Section: индукция овуляции при синдроме поликистозных яичниковunclassified